O corpo feminino e os ideais de beleza na publicidade sob um olhar da Psicanálise - Arlotta, Roberta Toste (2019)
The present study intends to investigate the effects of appropriation and overexposure of the feminine body as a sales tool in advertising campaigns in the social bond. Advertising plays an important role in the cultural industry, dictating consumer behavior and creating ideals of beauty. We have observed an evolution in the use of this body which is not only objectified and hypersexualized, but also digitally manipulated, fragmented and assembled as a puzzle. This body is exposed as if it were a tangible reality and it is enough for women to follow the magic “recipes” promised by the media, to conquer the “perfect” body. However, this body seems to have no materiality, it’s just a montage made virtually to attract the gaze and desire of your target. Today, women seem to be more submitted to beauty industry then men, they seem to be under pressure more often to respond to these cultural ideals. There is an attempt at equivalence between beauty and femininity, as a condition of being recognized as a woman in the society. Our objective is to investigate the effects of the exploitation of the feminine image in advertising campaigns, through a bibliographical review based on Freud’s and Lacan’s theories, articulating what we observe in the scope of cultural and what is strucutural in the alienantion with the Other